Repurposing the Industrial Dye Methylene Blue as an Active Component for Redox Flow Batteries. Issue 22 (30th August 2018) - Kosswattaarachchi, Anjula M.; Cook, Timothy R.
Abstract: Methylene blue is a common component of industrial wastewater in the textile industry. The redox properties of this environmentally damaging molecule make it suitable for use in the electrolyte solutions of aqueous redox flow batteries. Here, we carry out electrochemical analyses of aqueous methylene blue solutions to establish the dye as a pH tuneable, two‐electron redox transfer agent with fast transfer kinetics. Galvanostatic charge‐discharge experiments demonstrated ∼100 % coulombic efficiency for 50 cycles over seven days. Cycling performance was dependent on the membrane separator used. Cells containing an AMI‐7001 membrane showed a capacity decay with the state‐of‐charge falling to 56 % due to dye adsorption. Nafion NE1035 showed no adsorption nor membrane crossover. The combination of chemical and redox stability, and fast kinetics motivate the recycling of methylene blue wastewater as the basis for flow battery electrolyte solutions. Abstract : Upcycling of wastewater : the redox behaviour of methylene blue, a common textile dye is investigated for aqueous redox flow battery applications. The long‐term stability is established using bulk electrolysis experiments and membrane studies. Charge‐discharge experiments further demonstrate stable redox behaviour and high coulombic efficiencies.